Classification of non‐Hodgkin lymphoma in South‐eastern Europe: review of 632 cases from the international non‐Hodgkin lymphoma classification project. (27th July 2015) - Dotlic, Snjezana; Perry, Anamarija M.; Petrusevska, Gordana; Fetica, Bogdan; Diebold, Jacques; MacLennan, Kenneth A.; Müller‐Hermelink, Hans K.; Nathwani, Bharat N.; Boilesen, Eugene; Bast, Martin; Armitage, James O.; Weisenburger, Dennis D.
Summary The distribution of non‐Hodgkin lymphoma (NHL) subtypes varies around the world, but a systematic study of South‐eastern Europe (SEEU) has never been done. Therefore, we evaluated the relative frequencies of NHL subtypes in three SEEU countries – Croatia, Romania and Macedonia. Five expert haematopathologists reviewed 632 consecutive cases of newly diagnosed NHL from the three SEEU countries using the World Health Organization classification. The results were compared to 399 cases from North America (NA) and 580 cases from Western Europe (WEU). The proportions of B‐ and T‐cell NHL and the sex distribution in SEEU were similar to WEU and NA. However, the median ages of patients with low‐ and high‐grade B‐NHL in SEEU (60 and 59 years, respectively) were significantly lower than in NA (64 and 68 years, respectively; P < 0·05). SEEU had a significantly lower proportion of low‐grade B‐NHL (46·6%) and higher proportion of high‐grade B‐NHL (44·5%) compared to both WEU (54·5% and 36·4%, respectively) and NA (56·1% and 34·3%, respectively). There were no significant differences in the relative frequencies of T‐NHL subtypes. This study provides new insights into differences in the relative frequencies of NHL subtypes in different geographic regions. Epidemiological studies are needed to better characterize and explain these differences.